Optimal Sensor Placement for Accelerometer in Single-Pylon Cable-Stayed Bridge - Aminullah, Akhmad; Suhendro, Bambang; Panuntun, Raka Bagus (2022)
The construction of Indonesian cable-stayed bridges is developing nowadays. The most common approach for detecting bridge damage is the Structural Health Monitoring System (SHMS). The SHMS uses instrumentation equipment to monitor actions in the structure, including the cable-stayed bridge. In this study, the writer uses a single-pylon cable-stayed bridge as a case study, which is Soekarno Bridge in Manado, Indonesia. The accelerometer is one of the major sensors used in SHMS, as it can determine the bridge’s frequencies, damage detection, and the deterioration of the structures. This study exclusively reviews accelerometer sensors for bridge deck and only discusses vertical vibration since the vertical modes dominate this type of bridge. Optimal Sensor Placement (OSP) is a method to optimize the number and sensor position. The OSP processes the bridge's participation vector mode using several methods such as the Effective Independence Method, Eigenvalue Component Product, and Mode Shape Summation Plot Method, in which the accelerometer’s number and position are decided. The result shows that the Effective Independence Method has the most optimum number and sensor position based on the Fisher Information Matrix (FIM). The optimal number of accelerometers for the Soekarno Bridge deck is four (4) placed along the bridge deck. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.